Comparison of the Effectiveness of Four Bariatric Surgery Procedures in Obese Patients with Type 2 Diabetes: A Retrospective Study - Sylvie Pham; Antoine Gancel; Michel Scotte; Estelle Houivet; Emmanuel Huet; Hervé Lefebvre; Jean-Marc Kuhn; Gaetan Prevost (Hindawi Limited, 2014)
Aim. The aim of the present retrospective study was to evaluate the efficacy of four bariatric surgical procedures to induce diabetes remission and lower cardiovascular risk factors in diabetic obese patients. Moreover, the influence of surgery on weight evolution in the diabetic population was compared with that observed in a nondiabetic matched population. Methods. Among 970 patients who were operated on in our center since 2001, 81 patients were identified as type 2 diabetes. Laparoscopic adjustable gastric banding (GB), intervention type Mason (MA), gastric bypass (RYGB), and sleeve gastrectomy (SG) were performed, respectively, in 25%, 17%, 28%, and 30% of this diabetic population. Results. The resolution rate of diabetes one year after surgery was significantly higher after SG than GB (62.5% versus 20%, P<0.01), but not significantly different between SG and RYGB. In terms of LDL-cholesterol reduction, RYGB was equivalent to SG and superior to CGMA or GB. Considering the other cardiovascular risk factors, there was no significant difference according to surgical procedures. The weight loss was not statistically different between diabetic and nondiabetic matched patients regardless of the surgical procedures used. Conclusion. Our data confirm that the efficacy of surgery to treat diabetes is variable among the diverse procedures and SG might be an interesting option in this context.